1959
DOI: 10.1037/h0041003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of copulatory experience on mating behavior in the male rat.

Abstract: According to Beach (1942), the male rat's tendency to initiate coitus is controlled by a central excitatory mechanism (CEM) which reacts to sexual stimuli when selectively sensitized by an appropriate hormone (androgen). At a threshold excitatory level, the CEM discharges into motor centers which mediate copulation. The CEM may become reactive to normally inadequate stimuli after their repeated association, during copulation, with adequate sexual stimuli. The level of excitement is assumed to increase more rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1963
1963
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…The effects of sexual experience on mount and intromission latencies found in the present study are in agreement with results obtained with the male rat (Larsson, 1956;Rabedeau & Whalen, 1959). Differences in the frequency of ejaculation have not been reported for the rat, but die time-limited test employed in the rat studies make the number of ejaculations dependent upon the ICI and PEI (that is, the rate of ejaculation) which are relatively unaffected by sexual experience (Rabedeau & Whalen, 1959). Because of differences in the mating pattern and in testing procedures of the guinea pig, it is difficult to make quantitative comparisons between hamster and guinea pig.…”
Section: Comparison Of Hamster With Rat and Guinea Pigsupporting
confidence: 93%
“…The effects of sexual experience on mount and intromission latencies found in the present study are in agreement with results obtained with the male rat (Larsson, 1956;Rabedeau & Whalen, 1959). Differences in the frequency of ejaculation have not been reported for the rat, but die time-limited test employed in the rat studies make the number of ejaculations dependent upon the ICI and PEI (that is, the rate of ejaculation) which are relatively unaffected by sexual experience (Rabedeau & Whalen, 1959). Because of differences in the mating pattern and in testing procedures of the guinea pig, it is difficult to make quantitative comparisons between hamster and guinea pig.…”
Section: Comparison Of Hamster With Rat and Guinea Pigsupporting
confidence: 93%
“…Behavior is not simply a function of motivational state; behavior is a function of some interaction between motivation and habit (Wittenborn, 1957). In species such as the rat where habits usually contribute little to sexual behavior (Rabedeau & Whalen, 1959), measures of the behavior may allow relatively direct inferences about motivation. In carnivores and primates, habits greatly influence the expression of sexual behavior (Harlow, 1962;Rosenblatt & Aronson, 1958;Whalen, 1963a).…”
Section: Dimensions Of Sexualitymentioning
confidence: 99%
“…A role for previous sexual experience has been shown for both motivational (Kelliher and Baum, 2002; Matuszczyk and Larsson, 1994) and consummatory components of behavior [cats (Rosenblatt and Aronson, 1958) and hamsters (Lisk and Heimann, 1980)]. Although conflicting results were found for the effect of experience in the timing of the loss of mating behaviors in rats (Bloch and Davidson, 1968; Rabedeau and Whalen, 1959; Retana-Marquez and Velazquez-Moctezuma, 1997), it was shown that male rat copulatory behavior is more efficient after sexual experience. Compared to naïve animals, sexually experienced rats could achieve an ejaculation with fewer mounts and intromissions; those males with prior sexual experience had lower mount, intromission and ejaculation latencies (Bialy et al, 2000; Dahlof and Larsson, 1978; Dewsbury, 1969; Frankel, 1981; Pfaus and Wilkins, 1995) and lower post-ejaculatory interval (Larsson, 1959).…”
Section: Introductionmentioning
confidence: 99%